2019
DOI: 10.1111/rda.13441
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of reproductive hormone receptor expressions of the sheep ovary and hormone concentrations in two Chinese breeds

Abstract: The aim of this research was to investigate the changes in reproductive hormone receptor expressions of the ovary and hormone concentrations between oestrous cycle pattern of two different sheep breeds in China. Ovarian tissues were collected from Chinese Merino (Junken type) and Hu sheep with different reproductive states in spring and autumn. Serum samples were assayed for oestrogen (E2), progesterone (P), luteinizing hormone (LH) and follicle‐stimulating hormone (FSH) concentrations by radioimmunoassay duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“…Our results have clearly shown that LH concentration in hinds’ plasma was at a similar level during all analyzed seasons, but we did not analyze the preovulatory outflow period. Nevertheless, our results differ from the results obtained by Li et al 9 . In anestrus sheep, the concentration of LH in the serum was lower than during the reproductive season.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results have clearly shown that LH concentration in hinds’ plasma was at a similar level during all analyzed seasons, but we did not analyze the preovulatory outflow period. Nevertheless, our results differ from the results obtained by Li et al 9 . In anestrus sheep, the concentration of LH in the serum was lower than during the reproductive season.…”
Section: Discussioncontrasting
confidence: 99%
“…In the uterus and ovary, progesterone (P4) plays key physiological roles under the control of the pituitary hormones: luteinizing hormone (LH) and follicle-stimulating hormone (FSH) 9 and it affects the release of mature oocytes, supports implantation, maintains of pregnancy, and inhibits contractions of the myometrium 10 . During pregnancy, this steroid is synthesized by the corpus luteum, however, in the further stages of pregnancy, the placenta produces it in most mammal species, such as cow 11 , pig 12 , roe deer 13 , and human 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results have clearly shown that LH concentration in hinds' plasma was at a similar level during all analyzed seasons, but we did not analyze the preovulatory out ow period. Nevertheless, our results differ from the results obtained by Li et al [9]. In anestrus sheep, the concentration of LH in the serum was lower than during the reproductive season.…”
Section: Discussioncontrasting
confidence: 99%
“…Low levels of P4 during anestrus in goats and high levels of P4 in the luteal phase in sheep, during the middle of reproductive season, were observed by Thimonier [38]. In turn, Li et al [9] did not observe a luteal P4 peak in sheep during anestrus.…”
Section: Discussionmentioning
confidence: 92%
“…Low levels of P4 during anestrus in goats and high levels of P4 in the luteal phase in sheep, during the middle of reproductive season, were observed by Thimonier 38 . In turn, Li et al 9 did not observe a luteal P4 peak in sheep during anestrus. In comparison, our results showed a signi cant increase in P4 concentrations during the 13th day of the estrous cycle, while in the anestrus phase, this hormone's level was the lowest.…”
Section: Receptivity Of Uterus For P4 and E2 During The Estrous Cycle Anestrus And Pregnancymentioning
confidence: 89%